2016
DOI: 10.1016/j.rbmo.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sperm telomere length as a potential marker of paternal genome integrity and semen quality

Abstract: Recent studies have reported shorter sperm telomere length (STL) in men with idiopathic infertility. The aim of this study was to measure STL in semen samples from men to evaluate whether STL variation is associated with chromosomal abnormality, DNA fragmentation, traditional semen parameters, IVF outcome, or all four factors. A significant correlation between telomere length and diploidy was observed (P = 0.037). Additionally, STL was found to be positively associated with sperm count (P = 0.006); oligospermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 42 publications
5
76
4
Order By: Relevance
“…In this regard, significant correlations were reported between damaged DNA in spermatozoon with telomere length and protamine deficiency (Rocca et al, ; Tahamtan et al, ). Therefore, Cariati et al () proposed that assessment of sperm telomere length as a potential sign of chromatin integrity could be considered for infertile men (Cariati et al, ). On the other hand, a series of studies demonstrated that high level of oxidative stress can inversely effect DNA integrity and telomere length in spermatozoon (Cariati et al, ; Rocca et al, ; Tahamtan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, significant correlations were reported between damaged DNA in spermatozoon with telomere length and protamine deficiency (Rocca et al, ; Tahamtan et al, ). Therefore, Cariati et al () proposed that assessment of sperm telomere length as a potential sign of chromatin integrity could be considered for infertile men (Cariati et al, ). On the other hand, a series of studies demonstrated that high level of oxidative stress can inversely effect DNA integrity and telomere length in spermatozoon (Cariati et al, ; Rocca et al, ; Tahamtan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Cariati et al () proposed that assessment of sperm telomere length as a potential sign of chromatin integrity could be considered for infertile men (Cariati et al, ). On the other hand, a series of studies demonstrated that high level of oxidative stress can inversely effect DNA integrity and telomere length in spermatozoon (Cariati et al, ; Rocca et al, ; Tahamtan et al, ). Therefore, we aimed to access these three main factors; DNA fragmentation, protamine deficiency and lipid peroxidation (oxidative stress marker) in addition to telomere length in spermatozoa of fertile and infertile individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although telomere length is partially determined genetically and by paternal age, it is also influenced by internal and external environmental factors such as obesity, infection, oxidative stress, smoking, psychological and lifestyle stress, environmental factors and diet (Thilagavathi et al., ). However, currently, analysing sperm telomere length is not a part of standard clinical practice due to some conflicting data surrounding its relationship with sperm DNA fragmentation, sperm parameters and reproductive outcomes (Cariati et al., ; Lafuente et al., ; Rocca et al., ; Turner & Hartshorne, ; WHO, ). Thus, the validity of telomere length as a diagnostic tool of infertility and OS has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (16)(17)(18) reported that it was positively associated with sperm counts in semen. Another study (19) found that the sperm telomere length was negatively associated with sperm aneuploidy and DNA fragmentation. All of these studies showed that sperm telomere length was strongly associated with semen quality.…”
mentioning
confidence: 98%